The impact of face-to-face street fundraising on organizational reputation - Carolin J. Waldner; Jurgen Willems; Judith Ehmann; Felix Gies (International Journal of Nonprofit and Voluntary Sector Marketing, 2020)
Although many stakeholders perceive face-to-face street fundraising as unpleasant, nonprofit managers encourage it as a way to attract donors. To understand the long-term effects of this fundraising method, we used a mixed-methods experimental design to investigate how face-to-face street fundraising affects organizational reputation and stakeholder support intentions in comparison with letter fundraising. The findings reveal that face-to-face street fundraising has a significant negative influence on the stakeholders' perceptions of an organization. Further, qualitative data show that the negative perception originates primarily from perceived pressure, distrust, and obtrusion, which are triggered by face-to-face street fundraising. Our study thus reveals long-term reputational consequences that nonprofit organizations should consider before deciding on fundraising methods.
Keywords: 650